2022
DOI: 10.1111/jwas.12883
|View full text |Cite
|
Sign up to set email alerts
|

The role of aquafeeds in abalone nutrition and health: A comprehensive review

Abstract: Overpopulation and the pressure on land-based resources have driven the aquaculture sector to increase its production since the 1980s. To address such demands, new aquafeed technologies have been developed relying on natural and artificial ingredients that are commercially viable. In addition, current global sustainable initiatives require feed technologies to reduce the pressure on limited wild fisheries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 183 publications
0
21
0
Order By: Relevance
“…escalated amino acid assimilation and metabolic rate). 240,241 Such additional resources in this regard are allocable to other competing physiological processes (primarily immune activation). Compelling evidence revealed a reduced need for endogenous antioxidant enzymes in different fishes when supplemented with dietary carotenoids, but at the same time, enhancing their overall antioxidant status.…”
Section: Robust Modulation Of the Antioxidant Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…escalated amino acid assimilation and metabolic rate). 240,241 Such additional resources in this regard are allocable to other competing physiological processes (primarily immune activation). Compelling evidence revealed a reduced need for endogenous antioxidant enzymes in different fishes when supplemented with dietary carotenoids, but at the same time, enhancing their overall antioxidant status.…”
Section: Robust Modulation Of the Antioxidant Systemmentioning
confidence: 99%
“…The synthesis of antioxidant enzymes, including each enzyme‐catalyse event, typically requires investments from anabolic and catabolic processes within hosts (e.g. escalated amino acid assimilation and metabolic rate) 240,241 . Such additional resources in this regard are allocable to other competing physiological processes (primarily immune activation).…”
Section: Bioactivity and Related Mechanisms Of Carotenoids On The Str...mentioning
confidence: 99%
“…In recent years, the abalone production trend is increasing globally (Cook, 2016;Cook, 2019) and Korea is one of the major suppliers in the market (Cook, 2014). There are about 90 species of abalone (Bullon et al, 2022), six of which are found in Korean waters but aquaculture production dominantly comes from one species, the disk or Japanese abalone Haliotis discus hannai (Park and Kim, 2013;Cook, 2016). Large portions of abalone culture farms are located in the Wando County of South Jeolla Province comprising approximately 500,000 sea cages in the early 2010s (Park and Kim, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of produced abalone is consumed locally and some are exported to Japan, China, the USA, and Taiwan (Cook, 2016). Abalones are herbivorous organisms with a distinct shift in feeding pattern across life stages, from being planktivorous consuming microalgae during larval and post-larval stages and shifting to macroalgal diets starting at the juvenile stage (Takami and Kawamura, 2003;Bullon et al, 2022). The formulated feeds for abalone are sourced both from terrestrial and aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation